Fitting Statistical Distribution to Diameter and Resin Yield of Pinus roxburghii Stand - Bharti; Gupta, R. K.; Mahajan, P. K. (Indian Forester, 2019)
Statistical probability distributions are widely used in Forestry to model tree diameter distribution and to explain stand structure. The present investigation was carried out with the objective to fit probability distribution and find expected number of trees in diameter and yield classes. The data were collected on 145 trees for seven years w.e.f. year 2005 to year 2011 from natural regenerated Pinus roxburghii forest Solan Himachal Pradesh. Lognormal and gamma distributions were statistically fitted to observed diameter and resin yield. Kolmogorov-Smirnov test of goodness of fit indicated that these two distributions can be used to estimate number of trees in diameter classes. Also, lognormal distributions can be used to estimate number of trees in resin yield classes.